Assessment of Microbial Contamination Levels in Operating Rooms at Jalo Central Hospital - matterr, hamdy; M. Ayad, Tariq; M. El-Bashic, Aisha (Libyan Journal of Medical and Applied Sciences, 2026)
This study was conducted at Jalo Central Hospital JCH to evaluate the level of microbial contamination in surgical and orthopedic operating rooms. A total of 25 environmental swab samples were collected from enclosed surfaces in the operating rooms and OSR and cultured using sterile media. The results revealed an overall microbial contamination rate of 8%, which is comparable to contamination rates reported in previous studies, while markedly lower than others that reported substantially higher levels. Fungal contamination was detected in 20% of the contaminated samples, whereas no bacterial growth was observed in any of the collected samples (0%). Fungal growth was limited to two samples from the surgical operating room, primarily from the hands of medical staff and the medicine cabinet, each accounting for 8%. No bacterial or fungal contamination was recorded on operating tables, surgical instruments, door handles, sinks, or light fixtures. The absence of bacterial growth and the low fungal contamination rate indicate a high level of environmental cleanliness and effective infection control practices. These findings are attributed to efficient sterilization protocols, particularly the use of autoclave sterilization, along with strict hygiene and disinfection procedures. Overall, the results suggest that the operating room environment at JCH is well controlled microbiologically, thereby minimizing the risk of surgical site infections.